Trigenic ADH5/ALDH2/ADGRV1 mutations in myelodysplasia with Usher syndrome. Issue 8 (August 2021) - Kinoshita, Shintaro; Ando, Miki; Ando, Jun; Ishii, Midori; Furukawa, Yoshiki; Tomita, Osamu; Azusawa, Yoko; Shirane, Shuichi; Kishita, Yoshihito; Yatsuka, Yukiko; Eguchi, Hidetaka; Okazaki, Yasushi; et al.
Abstract: Trio-next generation sequencing is useful to identify undiagnosed inherited diseases. We have attended a patient with trigenic ADH5 / ALDH2 / ADGRV1 pathogenic variants, which caused two distinct diseases, myelodysplastic syndrome and Usher syndrome. Whole genome sequencing of peripheral blood from the patient and his parents were applied to identify disease-causing genes. Sanger sequencing was performed to validate the identified ADH5 / ALDH2 / ADGRV1 variants. Our results identified disease-associated variants in ADGRV1 (disease inheritance autosomal recessive) and in ADH5 (disease inheritance also autosomal recessive) and a variant in ALDH2 (disease inheritance autosomal dominant). Although the variants identified in ADH5 and ALDH2 have been reported, their co-existence in association with disease-causing variation in a third gene has not. They broaden the spectrum of ADGRV1 in Usher syndrome. Findings on next generation sequencing guided rapid and accurate diagnosis, resulting in patient-tailored therapeutic intervention. Highlights: Trigenic ADH5 / ALDH2 / ADGRV1 ​variants in myelodysplastic syndrome with Usher syndrome were identified. Two novel pathogenic frameshift variants in ​ ADGRV1 ​in compound heterozygous state with Usher syndrome type II were described. Findings on next generation sequencing guided rapid and accurate diagnosis, resulting in patient-tailored therapy. Abstract : ADH5/ALDH/ADGRV1 variants, Myelodysplastic syndrome, Trigenic mutations, Trio-next generation sequencing, Usher syndrome.